Whose voice really matters? Exploring the intra-household decision-making process in farm households of rural Bihar, India - Geetha, Rosalin (University of Agricultural Sciences, Bengaluru, 2023)
Empirical gender research on household decisionmaking has registered a significant expansion recently. While several of these studies indicate jointness in intrahousehold decision-making, the extent to which women’s perspectives are considered in the final outcomes remains uncertain. Equally crucial is understanding the explicit recognition of women’s contributions within patriarchal social systems by other household members. Against this backdrop, the present study empirically investigates women’s agency in making intrahousehold decisions pertaining to agricultural production and household consumption, considering both women’s and men’s perspectives. The study draws upon primary data collected from 414 maize-growing households (comprising 828 individuals) across 10 districts in Bihar, India. The findings reveal consistent patterns, highlighting men’s perception of women’s limited role and agency in farm production activities, in contrast to how women perceive themselves. Conversely, men predominantly reported women’s dominance in consumption decisions, while women refuted this claim, emphasizing joint decision-making involving other household members. Factors such as the husband’s migration status, caregiving responsibilities, and the presence of in-laws significantly and negatively impact women’s decisionmaking capacity. Moreover, households belonging to marginalized castes and communities exhibited higher levels of women’s agency. Regional disparities in women’s agency were also observed, indicating diverse dynamics influenced by social institutions, household structure, and asset ownership. These findings underscore the intricate and varied nature of gendered power dynamics within intrahousehold decision-making processes.